Workplace-Based Interventions for Neck Pain in Office Workers: Systematic Review and Meta-Analysis. Issue 1 (23rd October 2017) - Chen, Xiaoqi; Coombes, Brooke K; Sjøgaard, Gisela; Jun, Deokhoon; O'Leary, Shaun; Johnston, Venerina
Abstract: Background: At present, there is no consolidated evidence for workplace-based interventions for the prevention and reduction of neck pain in office workers. Purpose: The purpose of this review was to investigate the effectiveness of workplace-based interventions for neck pain in office workers. Data Sources: MEDLINE, PEDro, CINAHL, and CENTRAL were searched for trials published since inception and before May 31, 2016. Study Selection: Randomized controlled trials (RCTs) were considered when they met the following criteria: population consisted of office workers, intervention(s) was performed at the workplace, outcome measures included neck and/or neck/shoulder pain intensity and incidence/prevalence, and comparator groups included no/other intervention. Data Extraction: Data were extracted by 1 reviewer using predefined data fields and checked by a second reviewer. Risk of bias was assessed by 2 independent reviewers using the 2015 Cochrane Back and Neck Group guidelines. Evidence quality was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation system. Data Synthesis: Twenty-seven RCTs were included. There was moderate-quality evidence that neck/shoulder strengthening exercises and general fitness training were effective in reducing neck pain in office workers who were symptomatic, although the effect size was larger for strengthening exercises. Greater effects were observed with greater participation in exercise. Ergonomic interventions were supported by low-quality evidence. Limitations: Data could not be obtained from some studies for meta-analysis and assessment of risk of bias. Reporting bias might have been present because only studies in the English language were included. Conclusions: Workplace-based strengthening exercises were effective in reducing neck pain in office workers who were symptomatic, and the effect size was larger when the exercises were targeted to the neck/shoulder. Future RCTs of ergonomic interventions targeted at office workers who are symptomatic are required. More research on neck pain prevention is warranted.